2022
DOI: 10.3390/fluids7030110
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Reduced Order Modeling of Large Data Sets Obtained from CFD Simulations

Abstract: The ever-increasing computational power has shifted direct numerical simulations towards higher Reynolds numbers and large eddy simulations towards industrially-relevant flow scales. However, this increase in both temporal and spatial resolution has severely increased the computational cost of model order reduction techniques. Reducing the full data set to a smaller subset in order to perform reduced-order modeling (ROM) may be an interesting method to keep the computational effort reasonable. Moreover, non-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…All measurements discussed in this study, and shown on Figure 11, have a similar SPOD structure in which the precessing motion has the highest harmonic correlation and energy. According to Holemans et al (11), analysing coherent 3D structures based on 2D PIVmeasurements with SPOD introduces a maximum frequency deviation of 10% due to the loss of spatial information.…”
Section: Unsteady Flow Field Analysismentioning
confidence: 99%
“…All measurements discussed in this study, and shown on Figure 11, have a similar SPOD structure in which the precessing motion has the highest harmonic correlation and energy. According to Holemans et al (11), analysing coherent 3D structures based on 2D PIVmeasurements with SPOD introduces a maximum frequency deviation of 10% due to the loss of spatial information.…”
Section: Unsteady Flow Field Analysismentioning
confidence: 99%